Shastry-Sutherland kondo lattice model : interplay between frustration and the kondo effect - Su, Lei (2014)
The Kondo lattice model has its root in studying the properties of heavy Fermi liquids. Most previous work focused on the competition between the couplings of localized magnetic moments and the Kondo interactions of those local moments with itinerant electrons. Recent experimental observations discovered separation of antiferromagnetic phase boundaries from the small-large Fermi surface transition, suggesting that frustration may be an important factor for a complete phase diagram. In this final year project report, I present a mean field study of the Kondo lattice model on a Shastry-Sutherland lattice. If no Cooper channel is considered, the expected phase diagram for the model will be produced by using a direct diagonalization. In consideration of a recent proposal of possible superconductivity instabilities on the such a lattice, I also present a resonating-valence-bond-like mean field theory study with a Cooper channel decoupling. Strong numerical evidence supports the existence of a phase with both a condensation of spinon pairs and a dimer order of the Shastry-Sutherland lattice, when doped sufficiently. This discovery provides an important insight into the effect of frustration with the Kondo effect in heavy fermion systems.